THE ANTHROPOLOGICAL DIMENSION OF CONTEMPORARY SOCIETAL PROBLEMS IN THE CONTEXT OF THE ETHICS OF RESPONSIBILITY - Skyba, Іvan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Modern technological civilization has radically changed the scale, temporal horizon, and consequences of human action. As a result, the problem of responsibility has moved beyond the limits of individual moral evaluation and has become a central issue of philosophical anthropology and social ethics. The aim and tasks. The aim of the article is to analyze the transformation of the understanding of the human being as a moral subject under the conditions of technological civilization through the anthropological foundations of Hans Jonas’s ethics of responsibility. The tasks are to clarify the philosophical meaning of responsibility, to reveal the significance of the new categorical imperative, the principle of preserving the conditions of human existence, and the heuristic of fear, and to determine their explanatory potential for understanding the contradictions of modern society. Research methods. The study is based on the hermeneutic method, philosophical-anthropological analysis, comparative interpretation, and a systemic approach. Research results. It is shown that responsibility becomes oriented toward the future and toward preserving the very possibility of human life. The paper substantiates that technological risks, the institutional mediation of action, distributed responsibility, and the formation of a risk society should be interpreted as manifestations of a structural contradiction between increasing technical power and the insufficiency of moral and institutional mechanisms for controlling its consequences. Discussion. The results obtained confirm the productive potential of Jonas’s concept for interpreting the anthropological foundations of modern social problems. Conclusions. It is concluded that the ethics of responsibility should be understood as a way of anthropological rethinking of the human being in the technological age. The article establishes that the problems of modern society are not isolated crises but expressions of a deeper mismatch between the scale of human action and the ability to foresee and control its long-term consequences. This makes responsibility a fundamental principle for philosophical reflection on contemporary civilization rather than merely a secondary moral virtue.